Hubungan Efikasi Diri Dan Motivasi Kewirausahaan Calon Pensiunan Perusahaan Perkebunan Kelapa Sawit - Puriwara, Lisa Ariska; Pambudy, Rachmat; Etriya, Etriya; Ariska Puriwara, Lisa (Forum Agribisnis, 2025)
The world population is aging and almost every country in the world, including Indonesia, is experiencing growth in the number and proportion of older people in its population. Entrepreneurship research on retiree candidates can contribute to knowledge and efforts to deal with the aging population problem. Entrepreneurial self-efficacy and motivation are estimated to have a relation with older entrepreneurs' entrepreneurial decisions. The study aimed to analyze the correlation between self-efficacy and entrepreneurial motivation of prospective retirees of oil palm plantation companies. Data were obtained from a survey of palm oil company employees who will retire in 2024 to 2028, with a total sample of 119 respondents. Then the data were analyzed with Spearman Rank correlation analysis by STATA. The research findings show that entrepreneurial self-efficacy and motivation of retiree candidates are in the moderate category. The correlation test results show that self-efficacy is positively and strongly correlated with entrepreneurial motivation. This study suggests that companies prepare employees who will retire with training containing self-efficacy strengthening material because strong self-efficacy will motivate company employees who will retire to do entrepreneurship in retirement.